A risk score for pericarditis recurrence. (29th May 2021) - Lazarou, Emilia; Lazaros, George; Antonopoulos, Alexios S.; Imazio, Massimo; Vasileiou, Panagiotis; Karavidas, Apostolos; Toutouzas, Konstantinos; Vassilopoulos, Dimitrios; Tsioufis, Costas; Tousoulis, Dimitris; Vlachopoulos, Charalambos
Abstract: Background: Currently, we remain uncertain about which patients are at increased risk for recurrent pericarditis. We developed a risk score for pericarditis recurrence in patients with acute pericarditis. Materials and methods: We prospectively recruited 262 patients with a first episode of acute pericarditis. Baseline patients' demographics, clinical, imaging and laboratory data were collected. Patients were followed up for a median of 51 months (interquartile range 21‐71) for recurrence. Variables with <10% missingness were entered into multivariable logistic regression models with stepwise elimination to explore independent predictors of recurrence. The final model performance was assessed by the c‐index whereas model's calibration and optimism‐corrected c‐index were evaluated after 10‐fold cross‐validation. Results: We identified six independent predictors for pericarditis recurrence, that is age, effusion size, platelet count (negative predictors) and reduced inferior vena cava collapse, in‐hospital use of corticosteroids and heart rate (positive predictors). The final model had good performance for recurrence, c‐index 0.783 (95% CI 0.725‐0.842), while the optimism‐corrected c‐index after cross‐validation was 0.752. Based on these variables, we developed a risk score point system for recurrence (0‐22 points) with equally good performance (c‐index 0.740, 95% CI 0.677‐0.803). Patients with a low score (0‐7 points) had 21.3% risk for recurrence, while those with high score (≥12 points) had a 69.8% risk for recurrence. The score was predictive of recurrence among most patient subgroups. Conclusions: A simple risk score point system based on 6 variables can be used to predict the individualized risk for pericarditis recurrence among patients with a first episode of acute pericarditis.